Innovative Flipchart-Based Learning Media for Biology Education: A Developmental Research Study - Farhanah Farhanah; Ayu Ayu; Budi Budi; Vivin Yuliza (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to develop a flipchart-based learning media for biology education on ecosystem topics for seventh-grade students and to evaluate its feasibility and user responses for classroom implementation. Methodology: This study employed a Research and Development approach adapted from the Borg and Gall model. Data were collected through observations, interviews, documentation, and structured questionnaires. The instruments included content expert, language expert, media expert, teacher response, and student response questionnaires based on the Walker and Hess evaluation framework. Data were analyzed using descriptive quantitative techniques with percentage-based feasibility assessments. Main Findings: The developed flipchart-based learning media was successfully produced and evaluated. Media expert validation yielded a feasibility score of 84%, language expert validation reached 91%, and content expert validation achieved 58%. Teacher responses showed an average score of 71%, while student responses reached 63%. Overall, the developed learning media was categorized as feasible and received positive responses from both teachers and students, indicating its suitability for supporting biology learning activities. Novelty/Originality of this study: This study introduces a flipchart-based biology learning medium specifically designed for ecosystem learning at the junior secondary level. Unlike previous studies that predominantly focus on digital learning technologies, this research emphasizes a practical, low-cost, and visually structured instructional medium. The study contributes empirical evidence regarding the development process, expert validation, and user responses, thereby expanding knowledge on alternative learning media for biology education in resource-limited educational settings.